Effect of nutrition in Alzheimer’s disease: A systematic review - Xu Lou, Inmaculada; Ali, Kamran; Chen, Qilan (Frontiers in Neuroscience, 2023)
Background and objective Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by declining cognitive ability. Currently, there are no effective treatments for this condition. However, certain measures, such as nutritional interventions, can slow disease progression. Therefore, the objective of this systematic review was to identify and map the updates of the last 5 years regarding the nutritional status and nutritional interventions associated with AD patients. Study design A systematic review. Methods A search was conducted for randomized clinical trials, systematic reviews, and meta-analyses investigating the association between nutritional interventions and AD published between 2018 and 2022 in the PubMed, Web of Science, Scopus, and Cochrane Library databases. A total of 38 studies were identified, of which 17 were randomized clinical trials, and 21 were systematic reviews and/or meta-analyses. Results The results show that the western diet pattern is a risk factor for developing AD. In contrast, the Mediterranean diet, ketogenic diet, and supplementation with omega-3 fatty acids and probiotics are protective factors. This effect is significant only in cases of mild-to-moderate AD. Conclusion Certain nutritional interventions may slow the progression of AD and improve cognitive function and quality of life. Further research is required to draw more definitive conclusions.